TRADITIONAL RISK FACTORS AND PREDICTION OF CARDIOVASCULAR COMPLICATIONS IN PATIENTS WITH CHRONIC ISCHEMIC HEART FAILURE - N. A. Kosheleva; A. P. Rebrov (Klinicist)
Aim – to estimate the contribution of traditional risk factors in the development of cardiovascular complications (CVC) in patients with chronic heart failure (CHF) of ischemic genesis, the creation of predictive models of adverse outcome.Materials and methods. The study included 167 patients (144 men and 23 women) aged 40 to 72 years after myocardial infarction with manifestations of CHF and written informed consent signed. All patients underwent general clinical examination, a test with a 6-minute walk test, echocardiography, determination of levels of high sensitivity C-reactive protein (hsCRP), NT-proBNP (N-terminal fragment pro-brainnatriuretic peptide). Monitoring of patients lasted for 12 months with fixing the following end points: worsening of CHF, the development ofunstable angina and myocardial infarction, death, the total number of CVAE.Results. The development of the MTR during the year in patients with ischemic CHF is associated with age older than 60 years, body weight > 90 kg, heart rate (HR) > 70 beats/min, a distance of 6-minute test < 250 m, greater dilatation and faction ejection < 37 %, uric acid level > 250 umol/L, NT-proBNP > 250 pg/ml, hsCRP > 5.8 g/l. In the model predicting the development of the MTR in patients with ischemic CHF included age, body mass index, heart rate, uric acid levels, NT-proBNP, hsCRP, which are independent significant predictors of adverse outcome.Conclusion. The created model allows us to calculate individual risk for the MTR in patients with ischemic CHF during the year and make the correction of risk factors for improving prognosis. The sensitivity of this model is 81 % and specificity – 85 %.